Dosimetric and Radiobiological Impact of Patient Setup Errors in Intensity-modulated Radiotherapy for Esophageal Cancer - Jia-Huan Cai MS; Xun Peng BMed; Jia-Yang Lu MS (Technology in Cancer Research & Treatment)
Purpose To evaluate the impact of patient setup errors on the dosimetry and radiobiological models of intensity-modulated radiotherapy (IMRT) for esophageal cancer. Methods and materials This retrospective study with 56 patients in thermoplastic mask (TM) and vacuum bag (VB) groups utilized real setup-error (RSE) data from cone-beam CT scans to generate simulated setup-error (SSE) data following a normal distribution. The SSE data were applied to simulate all treatment fractions per patient by shifting the plan isocenter and recalculating the dose. A simulated plan sum (SPS) was created by accumulating all simulated fraction plans. Comparisons of target dose, improved homogeneity index (iHI), conformity index (CI), tumor control probability (TCP) and normal tissue complication probability (NTCP) were conducted between SPSs and original treatment plans (OTPs). Correlations between RSE and TCP/NTCP were analyzed. Results Compared to OTPs in the TM group, the planning target volume (PTV) of SPSs showed reductions in D 95% , D 98% , iHI, CI and TCP by 1.2%, 2.2%, 2.3%, 7.3% and 1.2%, while D 2% increased by 0.3%; D 2% of clinical target volume (CTV) increased by 0.2% ( P  < .05). In the VB group, D 95% , D 98% , iHI, CI and TCP of PTV decreased by 2.5%, 4.5%, 4.2%, 15.6% and 2.0%, with D 2% increasing by 0.5%; D 2% of CTV increased by 0.5% while D 98% decreased by 0.2% ( P  < .05). The dose of organs at risk (OARs) changed slightly in both groups. The mean and standard deviation of absolute RSE negatively correlated with the TCP of PTV, while the mean RSE positively correlated with the NTCP of lung and spinal cord. Conclusions Setup errors may reduce dose homogeneity and conformity, potentially reducing TCP of PTV and increasing NTCP, especially when mean RSE shifts the isocenter towards OARs. VB immobilization may result in relatively larger impacts of setup errors, but this needs future validation.